Effect of manufacturing process parameters on the compression and energy absorption properties of 4D-printed deformable honeycomb structure - Peng, Xiang; Han, Yang; Liu, Guoao; Li, Jiquan; Yi, Bing; Sa, Guodong; Jiang, Shaofei (Smart materials and structures, 2024)
Four-dimensional-printed deformable honeycombs can produce pro-programmed shape deformation and different properties under external stimuli, and the manufacturing process parameters are the dominant factors affecting the microstructure and properties of the manufactured honeycomb structures. Although many researchers have investigated the effects of manufacturing process parameters on the mechanical properties of printed materials, there is still a lack of research on the relationship between manufacturing process parameters and properties of honeycomb structures. Therefore, a novel honeycomb structures which has two configurations under temperature stimuli is proposed, and the optimum manufacturing processes for the printing of this honeycomb are selected considering the compression and energy absorption properties simultaneously. The novel honeycomb is designed and printed with fused deposition modeling technology, which have hexagonal configuration (Structure I) and semi-triangular configuration (Structure II) under external temperature stimulus. The energy absorption capacity of Structure I and compressive properties of Structure II are investigated under different manufacturing process parameters. The experimental results indicate that the layer thickness has the most significant impact on the mechanical performance of deformable honeycombs. The combination of a layer thickness of 0.2 mm, printing speed of 40 mm s −1 , and 100% infill density are the best process parameters for the novel deformable honeycomb structures.